Sociocultural developmental approaches to autobiographical memory. Issue 4 (11th January 2019) - Fivush, Robyn
Summary: The sociocultural developmental model of autobiographical memory development has been a highly generative theoretical framework over the past 30 years, garnering both a great deal of empirical attention and support. In this article, the author details the theoretical framework and reviews the empirical evidence that indicates that individual differences in maternal reminiscing style has profound and enduring implications for the development of autobiographical memory. Concurrent, longitudinal, and experimental intervention research has demonstrated that mothers who reminisce in more highly elaborated ways with their preschool children facilitate the development of more elaborate and coherent autobiographical memories.